Research.NET Web: uma aplicação para análise e exibição de redes de colaboração acadêmica utilizando grafos dinâmicos - Lopes, Érick Luiz Fonsêca; Borges, Eduardo N. (Anais da Escola Regional de Banco de Dados (ERBD); 2018: Anais da XIV Escola Regional de Banco de Dados, 2018)
This paper describes the development of a Web solution that allows the dynamic visualization of academic collaboration networks. The application uses data from the Lattes platform to identify and display the relationship between sets of researchers.